The child and the doctor's word - Gómez Gallego, Rocío (Medicina UPB, 1992)
In this paper medical and psychoanalytical dialectics are confronted. From their mutual Understanding a vast field results as it applies to the management of children patients in whom word symbolism plays a most significant role.
Keywords: Pediatrics; Psychoanalytical; child patient; the child and the medical word